2016
DOI: 10.1103/physrevc.93.044605
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic and near-target direct breakup ofLi6andLi7

Abstract: Background: 6,7 Li and 9 Be are weakly bound against breakup into their cluster constituents. Breakup location is important for determining the role of breakup in above-barrier complete fusion suppression. Recent works have pointed out that experimental observables can be used to separate near-target and asymptotic breakup. Purpose: Our purpose is to distinguish near-target and asymptotic direct breakup of 6,7 Li in reactions with nuclei in different mass regions. Method: Charged particle coincidence measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…The idea that breakup capture should peak backward of no-capture breakup is confirmed by classical dynamical model simulations of breakup [24]. The simulation was constrained to reproduce the individual no-capture breakup total cross sections (σ αα , σ αt , σ αd , σ αp ) as well as the measured relative energy distributions of the breakup fragments [20,21,28]. The resulting simulated no-capture breakup double differential cross-section distribution as a function of energy and angle is shown in Fig.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…The idea that breakup capture should peak backward of no-capture breakup is confirmed by classical dynamical model simulations of breakup [24]. The simulation was constrained to reproduce the individual no-capture breakup total cross sections (σ αα , σ αt , σ αd , σ αp ) as well as the measured relative energy distributions of the breakup fragments [20,21,28]. The resulting simulated no-capture breakup double differential cross-section distribution as a function of energy and angle is shown in Fig.…”
mentioning
confidence: 91%
“…Some works have suggested that breakup capture fully accounts for the suppression of complete fusion [19,25,26]. However, when the characteristic timescales of breakup are treated explicitly, and model inputs carefully constrained by experimental results for no-capture breakup [22,27,28], the simulations account for only a small fraction of the measured incomplete fusion cross section [29]. There is, therefore, great uncertainty regarding the mechanism producing the majority of the incomplete fusion products, the cause of suppression of complete fusion, and the consequences for weakly bound unstable isotopes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…where P BU is the probability of breakup, P L BU (R)dR is the probability of breakup in the interval R to R + dR, and α and β are constants determined from experimental results that vary for different systems [53,54]. This function is sampled to determine the position of breakup in the orbit of the projectile [49].…”
Section: A Backgroundmentioning
confidence: 99%
“…On the contrary, the coupling effects of breakup and/or transfer channels on the complete fusion (CF) suppress its cross section at energies above the Coulomb barrier and produce some enhancements at sub-barrier energies in comparison to the coupled channels calculations that do not take into account coupling effects [4][5][6][7][8]. Many efforts have been devoted to investigate the systematic of the CF features [9][10][11][12][13][14][15]. In these studies, one conclusion is that the suppression factor of the CF cross section at energies above the Coulomb barrier is independent of the mass of the target, and depends mainly on the projectile breakup threshold [9,10].…”
Section: Introductionmentioning
confidence: 99%